Giant Woolly Bear (larva), Giant or Great Leopard Moth (adult) Hypercompe scribonia (Stoll 1790) (Lepidoptera: Erebidae: Arctiinae) - Donald W. Hall (EDIS, 2014)
The giant leopard moth is our largest eastern tiger moth. It was formerly in the family Arctiidae, which now composes the subfamily Arctiinae in the family Erebidae. Giant leopard moths are nocturnal. Males are commonly attracted to lights at night. Sometimes dozens of males come to bright lights set out in good habitat. This 6-page fact sheet was written by Donald W. Hall and published by the UF Department of Entomology and Nematology, August 2014.